Designing An E-Learning Application At Sma Negeri 12 Pandeglang To Improve Learning Effectiveness Using Bootstrap Framework And Php - Aryono, Gagah Dwiki Putra; Setiawan, Ajis (PT ARRUS Intelektual Indonesia, 2025)
The advancement of information and communication technology has significantly influenced the education sector, especially in enhancing learning flexibility and accessibility. This study aims to design and develop a web-based e-learning application for SMA Negeri 12 Pandeglang to improve the effectiveness of the teaching and learning process. The development method used is the Waterfall model, consisting of analysis, design, implementation, testing, monitoring, and maintenance stages. The application was built using Bootstrap for responsive and user-friendly interface design, and PHP for server-side development, supported by a MySQL database. Data collection was carried out through observation, questionnaires, and document study to identify existing issues, including limited interaction between teachers and students, manual task management, and inadequate access to learning materials. The system includes features such as user-role-based login, online material upload and download, assignment submissions, and performance reports. Testing using the Black Box method shows that the application functions properly and meets user needs. This e-learning platform is expected to support digital learning transformation and serve as a practical solution for improving educational quality in rural schools.